Exploring the teaching and learning of circle geometry in rural schools - Mpheti, Vincent Molebogeng (University of the Free State, 2023)
This report presents a qualitative case study exploring the teaching and learning of circle geometry in rural schools. The study involved six educators and was carried out in Bohlabela District, Mpumalanga. Data was collected through lesson observations of six consecutive lessons during the content workshop, lesson observations during class visits, learners’ scripts, and semi-structured interviews with the educators. The Duval’s cognitive theory guided the study. The findings indicate that educators that participated in this study were able to teach the correct content following the annual teaching plan. Learners were able to complete tasks set on circle geometry during teaching and learning in the classroom. On the other hand, the educators could not emphasise the issue of composing and decomposing shapes, the application of visualising shapes before proving the theorems, the relationship of shapes within the orientation of the circle and encouraging learners in solving circle geometry problems. Learners could not solve geometric problems, provide statements and prove theorems. The findings of this study might be useful to all secondary school mathematics in improving the teaching and learning of circle geometry. This study recommends using the cognitive processes when teaching circle geometry and assessing learners in mathematics classrooms.
Dissertation (M.Ed.(Mathematics Education))--University of the Free State, 2023
Keywords: Circle geometry; Geometric spatial reasoning; Geometric theorems; Problem-solving; Cognitive processes